Does origin determine environmental impacts? Not for bamboos. Issue 2 (11th February 2019) - Canavan, Susan; Kumschick, Sabrina; Le Roux, Johannes J.; Richardson, David M.; Wilson, John R.U.
Abstract : Societal Impact Statement: Non‐native species can cause considerable negative impacts in natural ecosystems. Such impacts often are directly due to the fact that these species occur in habitats where they did not evolve. We explored this for bamboos and found that, contrary to the situation in many other plant groups, biogeographic origin was not a strong predictor of the type and severity of environmental impacts caused. We argue that impacts from bamboos are a response to land transformation and disturbance of forest habitats by humans. Therefore, the threats posed by bamboos to highly disturbed forest systems should be the same wherever bamboos are present or planted, and management should adopt similar approaches. Summary: Negative environmental impacts can result from the human‐mediated breakdown of biogeographic boundaries that historically shaped species distributions leading to rapid population expansions, that is, from biological invasions. However, the alteration of natural ecosystems by humans has created opportunities for both native and non‐native species to become weedy. We assessed whether origin status (native or non‐native) matters for the type and magnitude of environmental impacts caused by bamboos (Poaceae: Bambusoideae). We used a systematic global literature search and the International Union for Conservation of Nature's (IUCN) Environmental Impact Classification of Alien Taxa (EICAT) scheme as the basis for scoring impacts of bamboo species. We found that the type and severity of recorded impacts were similar in the native and non‐native ranges of weedy bamboos, and that the habitats in which impacts are most often reported (i.e., temperate and tropical forests) were also the same. Origin was not a strong predictor of environmental impacts for bamboos. Rather, impacts are likely to be a response to human‐mediated land transformation and disturbance of forests. Further research on the mechanisms whereby bamboos impact other species is needed to guide management strategies in their native ranges and as input to risk assessments for new introductions and plantings. Abstract : Non‐native species can cause considerable negative impacts in natural ecosystems. Such impacts often are directly due to the fact that these species occur in habitats where they did not evolve. We explored this for bamboos and found that, contrary to the situation in many other plant groups, biogeographic origin was not a strong predictor of the type and severity of environmental impacts caused. We argue that impacts from bamboos are a response to land transformation and disturbance of forest habitats by humans. Therefore, the threats posed by bamboos to highly disturbed forest systems should be the same wherever bamboos are present or planted, and management should adopt similar approaches.